Lemon juice - mediated synthesis of titanium dioxide nanoparticles with antioxidant and anti-inflammatory activity - Mary Sheloni Missier; R. Mahesh; S. Rajeshkumar; Karthik Shunmugavelu; Evangeline Cynthia Dhinakaran (Amaltea Medical Publishing House, 2023)
Plant compounds such as flavonoids, terpenoids, polyphenols, enzymes, and alkaloids are used as reducing agents in eco-friendly titanium dioxide nanoparticle manufacturing. In the current investigation, titanium oxide was converted into titanium dioxide nanoparticles with the application of a lemon extract. Amazingly, the process was also cheap, eco-friendly, and easy to implement. Seeing the white fluid change to a pale yellowish white allowed us to visually confirm that the nanoparticles had been successfully created. Transmission electron microscopy (TEM) and ultraviolet-visible spectroscopy were employed for further characterization. Nanoparticles of titanium dioxide were measured to be between 30 and 45 nm in size. In the DPPH assay, a titanium dioxide nanoparticle concentration of 50 L was shown to be optimal for antioxidant activity. The results of the bovine serum albumin denaturation experiment validated the green produced nanoparticles' dose-dependent anti-inflammatory effect. Consequently, the green synthetic titanium dioxide nanoparticles have great potential as an anti-inflammatory and antioxidant in future medicinal applications.